Female poverty unleashing their roots (TEL Tempo, Espaço e Linguagem, 2020)
Abstract: This paper aims to evaluate how poverty and some ways in which it is understood presents itself as having a higher incidence on women. Understanding how poverty is perceived, lived and confronted by people requires an analysis of the techniques and methodologies that situate and place the indicators of that. Whereas women represent half of the world's population and are among impoverished groups, the question arises here about how poverty and women are related and how culture contributes to this relationship and also to their permanence.Keywords: Poverty. Women. Gender. Instersectionality.